Adjectival Phraseological Units with the Parametric Component - A. Yarullina, Olesya; R. Kayumova, Albina; Pamies Bertrán, Antonio (International Journal of Criminology and Sociology, 2022)
The article is devoted to the comparative study of the Tatar and English adjectival phraseological units with the parametric component. Structural and semantic peculiarities are taken into consideration. The main methods of research are those of general linguistic methods and special linguistic methods. The purpose of the article is to find out common and specific features of the adjectival phraseological units with the parametric components in the English and Tatar languages. The investigation is based on the material from English and Tatar monolingual and polylingual dictionaries. The adjectival phraseological units of the Tatar language have not been studied enough. The Tatar and the English languages are structurally different and the study of the adjectival phraseological units with the parametric component is of great interest. Comparative and non-comparative adjectival phraseological units with parametric components have been analyzed in the article, the frequency of the structures in both of the languages was found out and the explanation of the phenomenon was searched for. Semantically the adjectival phraseological units with the parametric component may express negative or positive attitude to reality, spheres of life, communicative process, or to a person, and that depends on the usage of this or that parametric adjective of the antonymic pair. General and specific features have been found out as well as exceptions. Based on the data got from the research the conclusions on the structure and semantics of the adjectival phraseological units with the parametric component are presented in the article.